Comparative In Vitro Activity of Five Cephalosporin Antibiotics Against Salmonellae - Strausbaugh, Larry J. (1978)
The in vitro activities of five cephalosporin antibiotics against 121 strains of salmonellae were compared. Cefamandole and cefaclor were more potent than cefazolin, and these three drugs were more active than cephalothin and cephalexin.